Corneal inflammation and proliferative activity of cells of anterior epithelium in modeling bacterial keratitis and using amniotic membrane fixed with different techniques - E.V. Sereda; V.V. Vit; G.I. Drozhzhina; T.B. Gaidamaka (Journal of Ophthalmology, 2016)
Introduction. Molecular mechanisms of the effect of amniotic membrane (AM) on the inflammation and recover of the cornea have been investigated using various biological markers.